"Is that for here or to go?" Drive-Through Pediatric Vaccine Clinic as a Novel Approach during a Global Pandemic. (25th November 2023) - Patil, Sowmya; Kerby, Karalyn; Ramick, Amy; Criddle, Justin H.
Abstract: Objective: Routine childhood vaccination and well-child visits are essential for pediatric patients' preventative and public healthcare services. The COVID-19 pandemic had an immediate and significant decline in well-child visits and vaccine administration. A one-of-a-kind 'Drive-Through Vaccine Clinic' was established to improve the vaccination rate and alleviate parental anxiety about being exposed to COVID-19 infection. Methods: Our initial focus was on children between 18 months – 4 years of age at the start of the pandemic, and then extended this to the back-to-school vaccines and the Influenza vaccines. Results: The Drive-Through Immunization Station provided 745 vaccines to 415 patients between April and September, 2020. The median wait time involved from patient arrival to completion of vaccine administration was 5 minutes at the Drive-Through location. Patient and parent feedback was positive. The addition of the Drive-Through Clinic helped to significantly increase the total number of vaccines administered compared to the previous year. Conclusion: In a global pandemic, innovative ideas to increase access to preventive healthcare should be a priority. In the future, this method of non-traditional vaccine administration, will allow for improved outreach efforts to underserved populations in our communities, and better disaster preparedness.